Mode Choice between Private and Public Transport in Klang Valley, Malaysia. (19th February 2014) - Chiu Chuen, Onn; Karim, Mohamed Rehan; Yusoff, Sumiani
Abstract : In 2010, Klang Valley has only 17% trips each day were completed using public transport, with the rest of the 83% trips were made through private transport. The inclination towards private car usage will only get worse if the transport policy continues to be inefficient and ineffective. Under the National Key Economic Area, the priority aimed to stimulate the increase of modal share of public transport in the Klang Valley to 50% by 2020. In the 10th Malaysia Plan, the Klang Valley Mass Rapid Transit was proposed, equipped with 141 km of MRT system, and will integrate with the existing rail networks. Nevertheless, adding kilometers into the rail system will not help, if people do not make the shift from private into public transport. This research would like to assess the possible mode shift of travellers in the Klang Valley towards using public transport, based on the utility function of available transport modes. It intends to identify the criteria that will trigger their willingness to make changes in favour of public transport as targeted by the NKEA.